Deep Breathing Relaxation for Decreasing Blood Pressure in People with Hypertension - Rahmatul Fitriyah; Gratsia Victoria Fernandez; Wahyu Sukma Samudera; Hidayat Arifin; Shenda Maulina Wulandari (Jurnal Ners, 2019)
Various non-pharmacological therapies can be used to reduce blood pressure. One of them is deep breathing relaxation. This study aimed to know the influence of deep breath relaxation to decrease the blood pressure of people with hypertension. The design of this study was an Pre-Experimental One Group Pretest-Post-test design which covered 30 respondents as the sample. They fulfilled the inclusion criteria and were chosen through purposive sampling. The independent variable in this study was deep breath relaxation and the dependent variable was blood pressure. The data collection technique was using the observation sheet of blood pressure measurement. Data were analyzed using the paired t test. The findings of this study majority there were decrease blood pressure after deep breath. Before doing the breath relaxation exercise, most of the respondents were hypertension level 1. Nonetheless, after the deep breath relaxation had been executed, most found that their blood pressure decreased although several respondents were at hypertension level 2 with stable blood pressure. The results showed that there were differences in the blood pressure patients with hypertension before and after the deep breath relaxation. There were several points which influenced the decrease in blood pressure after implementing the deep breath relaxation such as stress, cigarettes etc.